2017
DOI: 10.1093/mnras/stx1118
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a hot accretion flow in the presence of outflow and convection with large ordered magnetic field

Abstract: Hydrodynamics and magnetohydrodynamic simulations of hot accretion flow have indicated that there is an inward decreasing of mass accretion rate with decreasing radius. Consequently, we have a flatter density profile (ρ ∝ r −p with p ∝ 1.5 − s in the case ofṀ ∝ r s , 0 s < 1) compared to the case of a constant accretion rate ((ρ ∝ r − 3 2 ). In order to describe this behavior two models have been proposed: inflow-outflow solution and convection-dominated accretion flows. We have studied the properties of a hot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…We know that the ratio of the radial viscous force to the radial component of thermal pressure gradient for an accretion disc is proportional to (H/r) 2 in which H is the disc half-thickness (Frank et al 2002). Since the advectiondominated discs are geometrically thick, i.e., H/r ∼ 1, the radial viscosity may play a significant role in determining the properties of such discs (see also equation (32)).…”
Section: Introductionmentioning
confidence: 99%
“…We know that the ratio of the radial viscous force to the radial component of thermal pressure gradient for an accretion disc is proportional to (H/r) 2 in which H is the disc half-thickness (Frank et al 2002). Since the advectiondominated discs are geometrically thick, i.e., H/r ∼ 1, the radial viscosity may play a significant role in determining the properties of such discs (see also equation (32)).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of poloidal field component in an ADAF in the absence of outflows has been examined by Zhang & Dai (2008). Adopting the ideal magnetohydrodynamic (MHD) approximation, they concluded that the poloidal field component can reduce the temperature (see also Ghasemnezhad 2017). But Bu, Yuan, & Xie (2009) showed that the role of poloidal field component in the temperature reduction can be more significant when the outflows are considered (see also Mosallanezhad, Khajavi, & Abbassi 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Possibility of suppressing magnetic field reversals in accretion disks due to accretion was discussed in [42]. Also we mention works [43,44] devoted to modeling the relationship between convection and magnetic field in accretion disks. The effect of convective flows is essential for the evolution of magnetic fields in galaxies.…”
Section: Convection In Astrophysicsmentioning
confidence: 99%